Self-cleaning-radiation refrigeration-deicing integrated functional coating as well as preparation method and application thereof
By preparing integrated functional coatings of self-cleaning, radiation refrigeration and deicing on the surface of solar panels, the problems of sand and snow covering the surface of solar panels and overheating of the panels in summer are solved, and efficient dust prevention, cooling and deicing effects are achieved.
Patent Information
- Application Number
- CN202411935262.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art is difficult to solve the problems of sand and dust and ice covering on the surface of solar panels and overheating of panels in summer.
ITO films were prepared by magnetron sputtering method, and PDMS-SiO2 sol was prepared by plasma treatment and sol-gel method, spin-coated on the ITO film, combined with low surface energy modifiers, and integrated functional coatings from cleaning, radiation refrigeration and deicing were prepared.
The self-cleaning, cooling and deicing functions of solar panel surfaces are realized, the light transmittance and power generation efficiency of photovoltaic modules are improved, the adhesion of dust and ice and snow is reduced, and the adhesion and transparency of the coating are enhanced.
Smart Images

Figure CN119735384A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a self-cleaning-radiation cooling-deicing integrated functional coating and a preparation method and application thereof, belonging to the technical field of functional protective coatings and preparation thereof. Background Art
[0002] Solar power generation technology has the advantages of high reliability, low cost, and no restrictions on resource distribution and region. It is the development trend for humans to directly obtain clean energy. At present, the problem of dust accumulation on the surface of photovoltaic panels is becoming increasingly serious, affecting the transmittance of photovoltaic modules. Dust entering the interior of solar cells will cause serious damage to their components. Part of the sunlight is absorbed by the dust on the surface to generate heat, which is transferred to the solar cell, further increasing the surface temperature, causing the lattice expansion of the photovoltaic material, the reduction of the band gap, the increase of the reverse current density (J0), and the decrease of the photoelectric conversion efficiency. Studies have shown that for every 10°C increase in temperature, the photoelectric conversion efficiency of crystalline silicon cells will decrease by 4% to 5%. In addition, the problem of surface icing of solar cells in winter will also reduce the surface transmittance of solar panels, resulting in reduced power generation efficiency, and the output loss can be as high as 100%. Therefore, it is very important to protect the surface of solar panels from self-cleaning, cooling and deicing.
[0003] Scientists have studied a variety of methods to reduce dust, ice and snow coverage on the surface of solar panels, as well as the problem of overheating of solar panels in summer. Among them, the robot dust removal method can clean the dust on the surface of solar panels, but it requires matching charging devices, maintenance equipment and systems. The manual de-icing method can clean the surface ice and snow on time, but the de-icing efficiency is low, the labor cost is too high, and it is easy to damage the solar panels. Jet impact cooling technology can be used for heat dissipation, but because solar cells are generally built in plateau desert areas, water resources are relatively scarce, and it is not suitable for use in some solar power stations. In summary, there is currently a lack of a solution that can simultaneously solve the problems of dust, ice and snow coverage, and overheating of solar panels in summer.
[0004] In this regard, the preparation of a multifunctional coating that integrates self-cleaning, radiation cooling, and deicing is expected to solve the above problems. The coating protection method has little effect on the performance of solar panels, and has the advantages of simple preparation, low cost, and the ability to integrate multiple functions. Therefore, by coating the surface of solar cells with special materials, the adhesion of dust particles is reduced and the impact of dust on solar cell equipment is reduced. At the same time, the coating material can be improved so that the coating has radiation cooling and electric heating properties. It is very necessary to provide a functional film and its preparation method that can effectively prevent dust adhesion, ice and snow coverage, and reduce the surface temperature of solar panels. Summary of the invention
[0005] Aiming at the problems that the surface of existing solar panels is easily covered by dust, ice and snow during application, and the panels overheat in summer, the present invention provides a self-cleaning-radiation cooling-deicing integrated functional coating and its preparation method and application.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a method for preparing a self-cleaning-radiative cooling-deicing integrated functional coating, which specifically comprises the following steps:
[0008] (1) The ITO film is prepared by magnetron sputtering and then annealed for later use;
[0009] (2) pre-treating the surface of the annealed ITO film by plasma treatment;
[0010] (3) Preparation of PDMS-SiO2 sol by sol-gel method;
[0011] (4) The PDMS-SiO2 sol is spin-coated on the pretreated ITO film, heat-treated in an air atmosphere, and then immersed in a low surface energy modifier solution for modification and heated for curing to obtain a self-cleaning / radiative cooling / deicing coating.
[0012] It is further defined that the process parameters for preparing ITO thin film by magnetron sputtering in (1) are: the target material is a mixture of In2O3 and SnO2 with an atomic percentage of 90:10, the coating temperature is 280-600°C, the argon flow rate is 50sccm, the oxygen flow rate is 0-0.3sccm, the target-substrate distance is 10-20cm, and the sputtering power is 23-38W.
[0013] It is further defined that the coating temperature is 360°C.
[0014] It is further defined that the coating temperature is 440°C.
[0015] It is further defined that the coating temperature is 520°C.
[0016] Furthermore, the oxygen flow rate is defined as 0.1 sccm.
[0017] Furthermore, the oxygen flow rate is limited to 0.2 sccm.
[0018] It is further defined that the target-substrate distance is 15 cm.
[0019] Furthermore, the sputtering power is limited to 28W.
[0020] Furthermore, the sputtering power is limited to 33W.
[0021] It is further defined that the substrate for preparing the ITO film is a 3 cm×3 cm quartz glass test piece which is ultrasonically cleaned with anhydrous ethanol, acetone, deionized water and anhydrous ethanol for 10 to 30 minutes in sequence and then placed in a beaker filled with anhydrous ethanol for standby use.
[0022] It is further defined that the annealing treatment temperature in (1) is 300-400°C and the time is 30 minutes.
[0023] It is further defined that the thickness of the ITO film obtained in (1) is 40 to 400 nm.
[0024] Furthermore, (1) the thickness of the obtained ITO film is 100 nm.
[0025] It is further defined that the thickness of the ITO film obtained by (1) is 135 nm.
[0026] It is further defined that the thickness of the ITO film obtained by (1) is 185 nm.
[0027] It is further defined that the thickness of the ITO film obtained by (1) is 220 nm.
[0028] It is further defined that the plasma treatment parameters in (2) are: the gas type is oxygen, the flow rate is 5 slpm, the power is 80 W, and the time is 5 min.
[0029] It is further defined that the operation of (3) comprises the following steps:
[0030] Step 1, slowly adding hydrochloric acid / ethanol aqueous solution to tetraethyl silicate / ethanol solution, stirring and sealing for aging to obtain SiO2 sol;
[0031] Step 2, adding SiO2 / ethanol solution to SiO2 sol, adding zirconium beads, stirring, and ultrasonically dispersing to obtain SiO2-ethanol sol;
[0032] Step 3, grinding and ball-milling the solidified PDMS in sequence to obtain a PDMS solution, and mixing the PDMS solution with SiO2-ethanol sol to obtain a PDMS-SiO2 sol.
[0033] It is further defined that the tetraethyl silicate / ethanol solution in step 1 is prepared by mixing tetraethyl silicate and anhydrous ethanol in a molar ratio of 1:6 to 10.
[0034] It is further defined that the molar ratio of tetraethyl silicate, water and hydrochloric acid in step 1 is 1:4:0.05.
[0035] It is further defined that the molar ratio of tetraethyl silicate to anhydrous ethanol is 1:7.
[0036] It is further defined that the molar ratio of tetraethyl silicate to anhydrous ethanol is 1:8.
[0037] It is further defined that the molar ratio of tetraethyl silicate to anhydrous ethanol is 1:9.
[0038] It is further defined that the aging time in step 1 is 6 to 10 hours.
[0039] It is further limited that the aging time is 8 hours.
[0040] It is further defined that the SiO2 / ethanol solution in step 2 is formed by mixing hydrophobic SiO2 with a particle size of 15 nm and anhydrous ethanol in a mass ratio of 1:60 to 70.
[0041] It is further defined that the mass ratio of SiO2 / ethanol solution to SiO2 sol in step 2 is 1:8-14.
[0042] It is further defined that the mass ratio of SiO2 / ethanol solution to SiO2 sol is 1:10.
[0043] It is further defined that the mass ratio of SiO2 / ethanol solution to SiO2 sol is 1:12.
[0044] It is further defined that in step 3, the PDMS curing temperature is 300-400° C. and the curing time is 4-6 hours.
[0045] It is further defined that the grinding treatment in step 3 is to mix the solidified PDMS, ethanol and zirconium beads in a mass volume ratio of 5g:20mL:20g and then grind them, and the obtained grinding liquid is dried at 60-80°C for 4h to obtain slightly yellowish particles.
[0046] It is further defined that the grinding treatment in step 3 is: mixing the yellowish particles obtained by grinding with ethanol at a mass volume ratio of 2.5 g:10 mL, and then ball milling with zirconium beads for 20 hours to obtain a PDMS solution.
[0047] It is further defined that the mass ratio of PDMS to SiO2-ethanol sol in the PDMS-SiO2 sol obtained in step 3 is 1:2-10.
[0048] It is further defined that the mass ratio of PDMS to SiO2-ethanol sol is 1:4.
[0049] It is further defined that the mass ratio of PDMS to SiO2-ethanol sol is 1:6.
[0050] It is further defined that the mass ratio of PDMS to SiO2-ethanol sol is 1:8.
[0051] It is further defined that the spin coating speed in (4) is 2000-4000 rpm and the time is 15 s.
[0052] Furthermore, the spin coating speed is 3000 rpm.
[0053] It is further defined that the heat treatment temperature in (4) is 550°C and the time is 2 to 4 hours.
[0054] It is further defined that the low surface energy modifier in (4) is 1H,1H,2H,2H-perfluorodecyltriethoxysilane, methoxytrimethylsilane, octyltrimethoxysilane, octadecyltrichlorosilane, hexamethyldisilazane or octadecyltriethylsilane.
[0055] It is further defined that the low surface energy modifier solution in (4) is prepared from a low surface energy modifier and n-hexane, with a mass concentration of 1 to 4%.
[0056] It is further defined that the soaking time in (4) is 0.5 to 2 hours.
[0057] It is further defined that the heating curing temperature in (4) is 80° C. and the time is 15 to 30 minutes.
[0058] The second object of the present invention is to provide a self-cleaning-radiant cooling-deicing integrated functional coating prepared by the above method.
[0059] The third object of the present invention is to provide the above-mentioned self-cleaning-radiative cooling-deicing integrated functional coating, which is specifically used for the surface protection of solar panels.
[0060] Beneficial effects:
[0061] The present invention firstly adopts magnetron sputtering technology to prepare the ITO heating coating, and uses plasma to pre-treat the surface of the ITO coating, introduces more polar groups, and then spin-coats the PDMS-SiO2 modified sol on the surface. After curing treatment, the ITO heating coating has hydrophobicity and radiation cooling properties. In order to further reduce the surface energy of the coating, a n-hexane solution of perfluorosilane is used to reduce the surface energy of the coating, thereby obtaining a self-cleaning / radiation cooling / deicing integrated coating with high adhesion and high transparency. Compared with the prior art, the present invention also has the following advantages:
[0062] (1) The present invention adopts DC magnetron sputtering to prepare the ITO heating coating. 4+After the addition of In2O3 and high temperature annealing, the internal molecules of SnO2 are rearranged, and the small grains in the film are reduced in roughness by merging and growing, and the residual stress and defects in the film are eliminated, and the surface morphology is further improved, and the scattering of electrons at the grain boundaries is reduced, thereby increasing the mobility of carriers and enhancing the conductivity of the film. In addition, the conductivity mechanism of ITO coating is that In2O3 is a high-bandgap semiconductor material with a body-centered cubic iron manganese ore crystal structure at room temperature, and the hexacoordinated In 3+ The ion is located at the center of the cube, and the four-coordinated O 2- The ions are at the top, which has high transmittance and good conductivity. 4+ Ion, Sn 4+ Ion replacement In 3+ ions, each replacement can contribute an electron to the conduction band, enhancing the conductivity and chemical stability of the material, making the ITO material have a lower square resistance, thereby achieving the deicing performance of the material.
[0063] In addition, by setting appropriate parameters such as coating temperature, oxygen flow rate, target-substrate distance and sputtering power, ITO coatings of different thicknesses can be produced and uniform preparation of the ITO coating can be achieved.
[0064] (2) The present invention uses plasma treatment to destroy chemical bonds using high-energy electrons in low-temperature plasma, forming free radicals on the surface of ITO. When exposed to an oxygen-containing atmosphere, the surface is activated to form hydroxyl peroxides, introducing more polar groups, thereby increasing the bonding strength with the upper PDMS-SiO2 composite material. At the same time, O2 plasma can open the olefinic bonds of the monomers for graft polymerization, and introduce more polar groups, such as -COOH, -NH2, epoxy groups, etc., on the surface of the substrate. These groups are reactive groups, which improve the bonding force between ITO and the surface of the upper PDMS-SiO2 composite material, thereby increasing the bonding strength with the upper PDMS-SiO2 composite material.
[0065] (3) The present invention adopts a sol-gel method, selects tetraethyl silicate (TEOS) as a precursor, anhydrous ethanol as a solvent, uses an acid catalyst, and the hydrolysis reaction plays a major role in the reaction process. The main component of the prepared sol is Si(OH)4, which forms a linear chain to better coat the SiO2 particles. The porous SiO2 is in the form of granular clusters, and a granular gel film with high porosity is prepared, which has good anti-transmission performance. Zirconium beads are added to the solution before stirring, so that the solution can be better dispersed during the stirring process, which not only reduces the possibility of generating large clusters, but also has less impact on the transmittance of the coating after the coating is prepared. The prepared PDMS-SiO2 coating with hydrophobicity and radiation cooling properties has almost no effect on the transmittance of the functional coating.
[0066] (4) The present invention adopts a phase separation method, utilizing the different volatilization rates of water and ethanol in the PDMS-SiO2 sol to drive the assembly of SiO2 in the sol, and construct a micro-nano rough structure on the surface of the ITO coating. When dust contacts the coating surface, the coating surface has a certain rough structure. The rough structure of the surface can reduce the contact area between the dust particles and the coating surface. Since the small-sized SiO2 is modified by a low surface energy modifier, the solid surface energy is low, and there is a low van der Waals force between the dust and the surface, showing low dust adhesion, thereby achieving the self-cleaning performance of the coating. In addition, a 1-4wt% perfluorosilane n-hexane solution is used to reduce the surface energy of the coating, further reducing the adhesion of dust particles.
[0067] (5) The present invention selects PDMS material as the main material of the transparent radiator because it has extremely high visible light transmittance and infrared radiation characteristics, and has the advantages of simple preparation, environmental friendliness, and industrial scalability. It is considered to be an ideal material for photovoltaic radiation cooling. -1 )、C-OH(1239~130cm -1 ) and Si-O-Si(1100cm -1 ) bonds have strong thermal emission potential. With the increase of the proportion of polydimethylsiloxane, the symmetric stretching vibration frequency of the CH bond increases, and the film absorbs a small part of the incident sunlight, which reduces the transmittance. As the number of Si-O-Si groups increases, the asymmetric stretching vibration generated is enhanced, which significantly improves the emissivity in the 10-11μm band in the atmospheric window, achieving radiative cooling and heat dissipation.
[0068] (6) The present invention performs ball milling heat treatment on PDMS. At a low temperature of 150-250°C, the main decomposition product is siloxane oligomer; at a medium temperature of 250-400°C, through thermal cracking reaction, part of the dimethylsiloxy units are released into dimethylsilane, and part of the molecules may undergo hydrolysis reaction to produce silanol; at a high temperature above 400°C, the thermal decomposition of PDMS becomes more intense, the chemical structure is significantly destroyed, and the silicon oxygen bond breaks to generate SiO2. By controlling the temperature to 300-400°C, it can be ensured that PDMS is fully cured without significant impact on performance, and its radiation cooling performance is maintained. During ball milling, the PDMS is dispersed to a large extent, no large-area clusters appear, and most of the particle size is nanometer-level, which is almost uniformly dispersed on the glass surface, effectively ensuring the transmittance while increasing the robustness of the coating. Moreover, the ball-milled PDMS is added to the SiO2 solution and then spin-coated on the glass surface for annealing. During the annealing process, oxidative cross-linking occurs, which will cross-link with silicon dioxide and sol to form bonds, increasing the bonding force between the two, thereby helping to increase the adhesion of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 AFM image of the PDMS-SiO2 sol prepared in Example 1;
[0070] Figure 2 This is the SEM image of the PDMS-SiO2 sol prepared in Example 1;
[0071] Figure 3 Visible light transmittance of the ITO / PDMS-SiO2 coating prepared in Example 1. DETAILED DESCRIPTION
[0072] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0073] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0074] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0075] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0076] Example 1
[0077] The process of preparing the self-cleaning-radiative cooling-deicing integrated functional coating (ITO / PDMS-SiO2) in this embodiment includes the following steps:
[0078] Step 1: Preparation of ITO coating
[0079] A 3cm×3cm quartz glass specimen was ultrasonically cleaned with anhydrous ethanol, acetone, deionized water and anhydrous ethanol for 15 minutes in sequence. The coating temperature was set to 520°C, the oxygen flow rate was 0.2sccm, the target-substrate distance was 15cm, the target material was a mixture of In2O3 and SnO2 with an atomic percentage of 90:10, the sputtering power was 33W, and a 100nm thick ITO sample was prepared at a deposition time of 8min. The sample was annealed in a 350°C tubular furnace for 30min to obtain an ITO coating.
[0080] Step 2: Preparation of PDMS-SiO2 sol
[0081] ① Take 5.21g of tetraethyl silicate and 4.02g of anhydrous ethanol and mix and stir. After 5 minutes, a stably dispersed solution a is obtained. Take 1.8g of deionized water, 2.07g of hydrochloric acid with a pH of 2 and 4.02g of anhydrous ethanol and mix and stir. After 5 minutes, a stably dispersed solution b is obtained. Under stirring conditions, solution b is slowly added to solution a, and solution A is obtained after stirring for 30 minutes. Solution A is sealed with plastic wrap and aged at room temperature for 6 hours to obtain SiO2 sol, in which the diameter of SiO2 particles is about 50nm.
[0082] ② Take 2g of hydrophobic SiO2 with a particle size of 15nm and add it to the sol. Add an appropriate amount of zirconium beads and stir for 4h. Then, ultrasonically disperse for 30min to obtain SiO2-ethanol sol.
[0083] ③ Weigh 10g of PDMS and heat it in a tube furnace at 350℃ for 5h. Put 5g of the cured particles in a mortar, add 20mL of ethanol solution and 20g of zirconium beads for the first step of grinding. Dry the ground solution in an oven at 70℃ for 4h to obtain slightly yellowish particles. Divide the particles into equal masses and place them in two ball mills for ball milling. At the same time, add 10mL of ethanol and use large zirconium beads to ball mill for 20h to obtain a PDMS solution. Take 3.5g of the solution and add it to SiO2-ethanol sol to obtain PDMS-SiO2 sol.
[0084] Step 3: Preparation of ITO / PDMS-SiO2 coating
[0085] ① The surface of the ITO coating obtained in step 1 was subjected to plasma treatment for 15 minutes. The specific plasma treatment parameters were: the gas type was oxygen, the flow rate was 5 slpm, and the power was 80 W to enhance the adhesion with the upper coating.
[0086] ②Set the spin coating speed to 3000rpm and the acceleration to 1500r / min 2 , time is 15s, the PDMS-SiO2 sol is spin-coated on the ITO coating and heat-treated at 550℃ for 3h.
[0087] ③ Use 2wt% perfluorosilane n-hexane solution to soak for 2h for hydrophobic modification, heat at 80℃ for 30min to cure, and obtain ITO / PDMS-SiO2 coating.
[0088] The microscopic morphology of the prepared ITO / PDMS-SiO2 coating was characterized, and the specific AFM images are shown in the figure. Figure 1 As shown by Figure 1It can be seen that the coating is formed by the accumulation of particles, with a roughness of Rq = 88.5nm. This microscopic rough surface is a necessary condition for super hydrophobicity and dustproofness. Figure 2 As shown by Figure 2 It can be seen that the microstructure of the PDMS-SiO2 coating is Figure 1 Similarly, almost no PDMS particles can be seen after ball milling. This is because after heat treatment at 550 °C, PDMS undergoes thermal cracking to generate short-chain PDMS, which forms a smooth coating with the sol.
[0089] The transmittance of the obtained ITO / PDMS-SiO2 coating was tested, and the results are as follows: Figure 3 As shown in the figure, it can be seen that the ITO / PDMS-SiO2 coating has good transmittance in the visible light band.
[0090] Comparative Example 1
[0091] The difference between this comparative example and Example 1 is that the plasma treatment in step ① is not performed in step 3, and the remaining process steps and parameter settings are the same as those in Example 1.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 1 is that the curing treatment of PDMS in step ③ is not performed in step 2, and the remaining process steps and parameter settings are the same as those in Example 1.
[0094] Comparative Example 3
[0095] The difference between this comparative example and Example 1 is that in this comparative example, only step 1 is performed to obtain the ITO coating.
[0096] Comparative Example 4
[0097] The difference between this comparative example and Example 1 is that step 1 is not performed, and in step 3, the cleaned quartz glass specimen is plasma treated and then spin-coated with PDMS-SiO2 sol, and the remaining process steps and parameter settings are the same as those in Example 1.
[0098] Comparative Example 5
[0099] The difference between this comparative example and Example 1 is that the treatments of steps ① and ② in steps 1, 2 and 3 are not performed, and the cleaned quartz glass specimen is only immersed in a 2 wt % n-hexane solution of perfluorosilane and heated at 80° C. for 30 min.
[0100] The coatings prepared in Example 1 and Comparative Examples 1 to 5 were subjected to performance tests, and specific test results of water contact angle, first dust removal angle, durability, deicing effect at 5V voltage and emissivity are shown in Table 1 below.
[0101] Table 1
[0102]
[0103] By comparing Example 1 and Ratio 1, it can be seen that after 100 consecutive dust removals in Example 1, there is still a low dust removal angle, which proves that after plasma treatment, the coating has a stronger bonding ability with the substrate, and the PDMS-SiO2 coating is not easy to fall off under continuous dust impact, thereby achieving effective bonding between the ITO layer and the PDMS-SiO2 coating interface.
[0104] Comparison of Example 1 and Comparative Example 235 shows that the PDMS-SiO2 coating is the key to achieving super hydrophobic and dustproof performance. At the same time, in Comparative Example 1 and Comparative Example 2, the coating that was not pre-cured at 350°C has no dust removal performance. This is because PDMS and ethanol are not miscible, and there is no PDMS component in the coating, resulting in failure to achieve super hydrophobic performance and poor dust removal and wear resistance.
[0105] By comparing Example 1 with Comparative Examples 4 and 5, it can be seen that the ITO film is a necessary condition for achieving deicing performance. By comparing the deicing time of Example 1 with Comparative Examples 1, 2 and 3, it can be seen that super-hydrophobic performance can improve deicing efficiency. This is due to the low adhesion characteristics of the super-hydrophobic surface. Ice can be easily detached from the surface after melting into water. Comparative Example 3 has no hydrophobic surface, and water droplets adhere to the surface. More time and heat are required to evaporate the water droplets to achieve complete deicing.
[0106] In addition, Example 1 has the best infrared emissivity, proving that the coating has excellent heat dissipation effect. In summer, compared with the uncoated or other control examples under the same conditions, the surface temperature is lower, which effectively improves the power generation efficiency.
[0107] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a self-cleaning, radiant cooling and deicing integrated functional coating, characterized in that: include: (1) The ITO film is prepared by magnetron sputtering and then annealed for later use; (2) pre-treating the surface of the annealed ITO film by plasma treatment; (3) Preparation of PDMS-SiO2 sol by sol-gel method; (4) The PDMS-SiO2 sol is spin-coated on the pretreated ITO film, heat-treated in an air atmosphere, and then immersed in a low surface energy modifier solution for modification, and heated and cured to obtain a coating.
2. The preparation method according to claim 1, characterized in that: (1) The process parameters for preparing ITO thin film by magnetron sputtering are as follows: the target material is a mixture of In2O3 and SnO2 with an atomic percentage of 90:10, the coating temperature is 280-600°C, the argon flow rate is 50sccm, the oxygen flow rate is 0-0.3sccm, the target-substrate distance is 10-20cm, and the sputtering power is 23-38W; the annealing temperature is 300-400°C and the time is 30min.
3. The preparation method according to claim 1, characterized in that: (1) The thickness of the obtained ITO thin film is 40 to 400 nm.
4. The preparation method according to claim 1, characterized in that: (2) The plasma treatment parameters are: the gas type is oxygen, the flow rate is 5 slpm, the power is 80 W, and the time is 5 min.
5. The preparation method according to claim 1, characterized in that: The operation of (3) includes the following steps: Step 1, slowly adding hydrochloric acid / ethanol aqueous solution to tetraethyl silicate / ethanol solution, stirring and sealing for aging to obtain SiO2 sol; Step 2, adding SiO2 / ethanol solution to SiO2 sol, adding zirconium beads, stirring, and ultrasonically dispersing to obtain SiO2-ethanol sol; Step 3, grinding and ball-milling the solidified PDMS in sequence to obtain a PDMS solution, and mixing the PDMS solution with SiO2-ethanol sol to obtain a PDMS-SiO2 sol.
6. The preparation method according to claim 5, characterized in that: The mass ratio of PDMS to SiO2-ethanol sol in the obtained PDMS-SiO2 sol is 1:2-10, the mass ratio of SiO2 / ethanol solution to SiO2 sol in SiO2-ethanol sol is 1:8-14, and the mass ratio of SiO2 to anhydrous ethanol in SiO2 / ethanol solution is 1:60-70.
7. The preparation method according to claim 1, characterized in that: (4) The medium and low surface energy modifier is 1H,1H,2H,2H-perfluorodecyltriethoxysilane, methoxytrimethylsilane, octyltrimethoxysilane, octadecyltrichlorosilane, hexamethyldisilazane or octadecyltriethylsilane.
8. The preparation method according to claim 1, characterized in that: (4) The medium heat treatment temperature is 550°C for 2 to 4 hours; the heating curing temperature is 80°C for 15 to 30 minutes.
9. A self-cleaning-radiative cooling-deicing integrated functional coating prepared by the method according to any one of claims 1 to 8.
10. An application of the self-cleaning-radiation cooling-deicing integrated functional coating according to claim 9, characterized in that: Used for surface protection of solar panels.
Citation Information
Patent Citations
Mesoporous SiO2 wear-resistant anti-reflecting coating for flexible substrate, and preparation method thereof
CN107629491A
Preparation method of glass surface anti-reflection coating
CN108249773A
Preparation method for durable, transparent and superhydrophobic coating applicable to plurality of substrates
CN108587447A
Preparation method of TiO2-SiO2@PDMS composite super-hydrophobic filter material
CN113047050A
Visible-near infrared frequency division type radiation refrigeration film based on bionic rose petal micro-nano structure as well as preparation method and application of visible-near infrared frequency division type radiation refrigeration film
CN114714692A
Cited By
Preparation method and application of PDMS brush grafted on surface of polymer material
CN120590674A